Archéologie et fouilles en contexte difficile - De Andreis, Sonia; Guillaume, Gwendoline; Salviani, Clément; Taieb, Juliette (Archéo.doct, 2023)
Archaeology and excavation in difficult contexts are the subject of this 16th volume of Archéo.doct, which stems from and completes the exchanges held during the 16th doctoral day of ED 112 at the University of Paris 1 Panthéon-Sorbonne in 2021. The twenty articles deal with archaeological excavation (preventive and programmed) in the face of natural, anthropic, cultural and administrative obstacles encountered by archaeologists. They illustrate and enrich the discussions initiated during the study day, giving each author the space to freely present his or her issues and adaptations in the face of difficulties that are rarely mentioned during meetings between archaeology and cultural heritage professionals, yet are omnipresent in archaeological practice. The main challenge of this publication lies in expressing an unspoken fact: all archaeologists face difficulties, which they tend to overcome by adapting and producing technical, human and scientific solutions. This volume presents, in selected thematic sections, the different points of view of a number of archaeologists, from the Antilles to the Indus Basin, from the wet valleys of the Escaut to the industrial wastes of the Val de Marne, not forgetting excavations in inhospitable contexts, in times of war, intensive urbanism or low political interest.